Insider Trading in Indonesia: Supporting the Policy Implementation of the Capital Market Efficiency - YUSUF, Chandra (Journal of Advanced Research in Law and Economics, 2016)
As a developing country, Indonesia requires capital from domestic and foreign investors to realize its economic potential. In order to gain the capital, Indonesia opened an opportunity for foreign investors to establish or own a company with Foreign Capital Investment (PMA). In addition, foreign investors are able to buy and control the company's stocks that have been listed on the stock market. Capital obtained in the capital market will help companies develop their potential. Companies can pay operating expenses, including the salaries of directors, commissioners and other staffs. Investors, both domestic and foreign, as stockholders will benefit after operating expenses are paid in advance. With the capital, the potential of the company to pay for itself and provide profits for stockholders become the real potential of the company.
Keywords: insider trading; Capital Market Efficiency; Foreign Capital Investment